The Influence of Organizational Change, Leadership Style, and Work Environment on Employee Productivity in the Pharmaceutical Industry of PT. KSP - Yiyip Ika Yasmitasari; Sylvia Sari Rosalina (Journal Research of Social Science, Economics, and Management, 2025)
Employee productivity plays a crucial role in determining organizational success, particularly in dynamic industries such as the pharmaceutical industry. This study investigates the influence of organizational change, leadership style, and work environment on employee productivity, focusing on PT KSP. Using a quantitative research approach, data were collected through a survey of 82 employees representing various age groups. This study employed regression analysis to examine the relationship between the independent variables (organizational change, leadership style, and work environment) and the dependent variable (employee productivity). The results showed that organizational change and work environment had a significant and positive effect on employee productivity. However, the influence of leadership style on productivity was positive but insignificant. These findings emphasize the importance of clear communication regarding organizational change and creating a supportive work environment and leadership approach to meet organizational needs. This study concludes that organizational change, leadership style, a well-structured work environment, and an ethical work culture are crucial for improving productivity. Practical recommendations include optimizing organizational change communication, workplace conditions, and adopting adaptive leadership strategies. Future research should explore mediating factors such as employee engagement and organizational culture to better understand these dynamics.